MBD2 regulates differentiation and function of Th17 cells in neutrophils- dominant asthma via HIF-1α - Li Xu; Wen J. Sun; Ai J. Jia; Lu L. Qiu; Bing Xiao; Lin Mu; Jian M. Li; Xiu F. Zhang; Yan Wei; Cong Peng; Dong S. Zhang; Xu D. Xiang (BMC, 2018)
Abstract Background T helper 17 (Th17) cells have proven to be crucial in the pathogenesis of neutrophils-dominant asthma. Hypoxia inducible factor-1α (HIF-1α) is involved in allergic responses in asthma. Our previous studies indicated that Methtyl-CpG binding domain protein 2 (MBD2) expression was increased in asthma patients. The aim of the present study is to understand how MBD2 interacts with HIF-1α to regulate Th17 cell differentiation and IL-17 expression in neutrophils-dominant asthma. Methods A neutrophils-dominant asthma mouse model was established using female C57BL/6 mice to investigate Th17 cell differentiation and MBD2 and HIF-1α expression regulation using flow cytometry, western blot or qRT-PCR. MBD2 and HIF-1α genes were silenced or overexpressed through lentiviral transduction to explore the roles of MBD2 in Th17 cell differentiation and IL-17 release in neutrophils-dominant asthma. Results A neutrophilic inflammatory asthma phenotype model was established successfully. This was characterized by airway hyperresponsiveness (AHR), increased BALF neutrophil granulocytes, activated Th17 cell differentiation, and high IL-17 levels. MBD2 and HIF-1α expression were significantly increased in the lung and spleen cells of mice with neutrophils-dominant asthma. Through overexpression or silencing of MBD2 and HIF-1α genes, we have concluded that MBD2 and HIF-1α regulate Th17 cell differentiation and IL-17 secretion. Moreover, MBD2 was also found to regulate HIF-1α expression. Conclusions Our findings have uncovered new roles for MBD2 and HIF-1α, and provide novel insights into the epigenetic regulation of neutrophils-dominant asthma.